The social reuse of confiscated goods. The criticality of the lombard model (Rivista di Studi e Ricerche sulla criminalità organizzata, 2016)
How the confiscated assets of the organized crime are managed in Lombardy? This article states that it is possible to theorize a Lombard model, which reflects the history of the relationships between Lombard culture and mafia phenomenon. The author notes, in fact, a cultural removal of the mafia's presence even after trials and State victory, and a substantial extraneousness of  Lombardy to the deepest sense of antimafia legislation and its challenges. In this context a particular management of assets wins, namely a model founded on the rent much more than on the social enterprise.key-words: mafia, Lombardy, confiscated assets, removal, challenge